The German approach to evaluate complaints about odour annoyance in indoor environments - M. David; K. Sucker; J. Hameister; F. Gerull; H. Grams; C. Röhl; K. Schröder; L. Brosig; A.M. Scutaru; M. Debiak; M. Kolossa-Gehring (Indoor Environments)
The perception of unusual or unexpected odours in indoor air can give rise to complaints about odour annoyance. These complaints are frequently accompanied by concerns for adverse health effects as a consequence of exposure to indoor air substances. The German Committee on Indoor Air Guide Values (AIR) developed a practical guidance on how to evaluate if the complaints about odour annoyance in indoor environments are reasonable and how to reduce odour exposure when a so-called odour guide value (OGV) is reached or exceeded. The AIR describes the procedure to derive odour guide values for relevant odorous substances in indoor air and recommends a graded approach of odour reduction measures.